Context-Aware Browsing for Hyper-Local News Data (CABHLND) - Daradkeh, Dr. Yousef Ibrahim; Namiot, Dmitri; Schneps-Schneppe, Manfred (International Journal of Interactive Mobile Technologies (iJIM), 2012)
This paper describes a new model for delivering hyper-local data to mobile subscribers. Our model uses any exiting or especially created Wi-Fi hot spot as presence sensor that can open access for some user-generated content. In our approach we can describe hyper local data as info snippets that are valid (relevant) for mobile subscribers being at this moment nearby some Wi-Fi access point. And an appropriate mobile service (customized browser) can discover that information to mobile users. Service builds on the fly dynamic web pages and lets mobile subscribers to browse hyper-local data only. As the possible use-cases we can mention for example delivering news and deals in malls, news feeds for office centers and campuses, Smart City projects, personal classifieds etc.